2015
DOI: 10.1055/s-0035-1547263
|View full text |Cite
|
Sign up to set email alerts
|

Carbohydrate Management in Athletes with Type 1 Diabetes in a 10 km Run Competition

Abstract: The aim of this study was to identify the real consumption of CHO during a 10 km competitive run, to compare data with the recommended quantities according to current guidelines, and to analyse the clinical events associated with these different amounts. Protocol 1: observational study including 31 athletes with T1D and 127 athletes without diabetes, comparing data taken from dietary records of CHO intake on the competition day. Protocol 2: single-blind randomized trial in 18 athletes with T1D, testing a pre-e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…The results presented herein expand the limited number of findings about glycemic control in the study athletes during endurance 32,33 and ultraendurance 30,31 competitions. Additionally, 73% of the blood glucose analyses showed that these athletes were in a zone where it was safe to exercise (90–250 mg/dL or 5.0–13.9 mmol/L).…”
Section: Discussionsupporting
confidence: 63%
“…The results presented herein expand the limited number of findings about glycemic control in the study athletes during endurance 32,33 and ultraendurance 30,31 competitions. Additionally, 73% of the blood glucose analyses showed that these athletes were in a zone where it was safe to exercise (90–250 mg/dL or 5.0–13.9 mmol/L).…”
Section: Discussionsupporting
confidence: 63%
“…Although glycemic and PA measurements of competitive-level exercise for people with T1D are available, [42][43][44][45] less is known about T1D adults being active at an amateur level. Some of our study's limitations were related to the measurement instruments used, given by the free-living conditions study design.…”
Section: Discussionmentioning
confidence: 99%
“…Some athletes with type 1 diabetes ingest low to moderate levels of carbohydrates during training and rest periods 4,6,7 ; however, this strategy becomes inefficient during long-distance events when high levels of carbohydrate (70–90 g·h -1 ) are ingested, aiming to prevent hypoglycemia and support performance. 4 When carbohydrate is consumed during exercise, there is an alteration of substrate utilization to energy provision, with a lower contribution of endogenous carbohydrate and a higher rate of exogenous carbohydrate oxidation.…”
Section: Introductionmentioning
confidence: 99%
“…4 In addition to daily challenges, maintaining normal glucose levels during different training protocols, especially during prolonged exercise events 4 and traveling, may present a major challenge for athletes with type 1 diabetes, 5 considering that factors other than insulin levels have an impact on glycemia, such as macronutrient intake and psychophysiological stress responses. 4 Some athletes with type 1 diabetes ingest low to moderate levels of carbohydrates during training and rest periods 4,6,7 ; however, this strategy becomes inefficient during long-distance events when high levels of carbohydrate (70-90 g•h -1 ) are ingested, aiming to prevent hypoglycemia and support performance. 4 When carbohydrate is consumed during exercise, there is an alteration of substrate utilization to energy provision, with a lower contribution of endogenous carbohydrate and a higher rate of exogenous carbohydrate oxidation.…”
Section: Introductionmentioning
confidence: 99%